Machine vision based height measuring system - Ramlee, Ridza Azri; Hashim, Nik Mohd Zarifie; Abdul Rahman, Rozeana; Aziz, Khairul Azha A (2014)
This paper presents a machine vision based height measuring system. The system will measure the height of a product based on the input from a webcam. The input image from the webcam will then be processed using image processing and then calculated to give the height of the product. In the market, there are many products that need to be measured whether the length or the height. These products also have different size and shape. There are several problems when using manual method for measuring such as man power will be needed at the station, longer time needed for measuring the product and the measurement may not be so accurate. This system aims to reduce these problems by developing a measuring system based on vision system.